"Proyecto de factibilidad para la implementación de un gimnasio tradicional en la parroquia Panguintza, cantón Centinela del Cóndor provincia de Zamora Chinchipe" - Condoy Narváez, Sheyly Dayana (2024)
The study entitled 'Feasibility project for the impletnentation of a traditional gymnasium in the parish of Paguintza, Canton Centinela del Condor, Zamora Chinchipe province' , had the following objectives: to cany out a market study to determine supply and demand; to prepare a technical study to determine the size, location and engineering of the project and the legal and adrninistrative organization of the company; a financial study to determine investment and financing; and finally a financial evaluation to determine the feasibility or otherwise of the project by means of financial indicators. The of research was exploratory and descriptive, where the quantitative approach was used, as well as the research techniques that allowed for the collection and interpretation of the information. Among the results, the technical study established an installed capacity of 99,840 services per year, and the financial study determined an investment of $37,462.88 dollars. To determine the feasibility of the project it was based on: Net Annual Value (NPV) of Sl 06,801. 03 obtaining a positive NPV; the Internal Rate of Return (IRR) is 68.15% higher than the opportunity cost rate; Benefit Cost Ratio (BCR) of 0.17 cents for every dollar invested; Capital Recovery Period (CRP) of 12 months, the Sensitivity Analysis supports the 2.54% increase in costs, with a sensitivity of 2.18%, and a decrease in income of 1.57%, finally it is concluded that it is feasible to implement the project thanks to the results obtained in the study.